Tyrosine-free amino acid mixture attenuates amphetamine-induced displacement of [11C]raclopride in striatum in vivo: a rat PET study. - Le Masurier, M; Houston, G; Cowen, P; Grasby, P; Sharp, T; Hume, S (2004)
Previous neurochemical and behavioural studies show that tyrosine depletion using a nutritionally balanced tyrosine-free amino acid mixture attenuates the dopamine-releasing and psychostimulant properties of amphetamine. Here we investigate the effect of a tyrosine-free amino acid mixture on striatal binding of [(11)C]raclopride, and amphetamine-induced [(11)C]raclopride displacement, using positron emission tomography in the rat. Rats were scanned for 60 min after an i.v. injection of approximately 11 MBq [(11)C]raclopride using a quad-HIDAC system. Amphetamine (2 mg/kg i.p., 30 min prior to scan) caused a 12% reduction in [(11)C]raclopride distribution volume ratio (DVR) compared to saline-injected controls. The tyrosine-free amino acid mixture (1 g/kg i.p.) caused a small (+7%) but statistically insignificant increase in [(11)C]raclopride DVR and attenuated, although it did not fully block, the amphetamine-induced reduction. These data are in keeping with previous neurochemical, immunocytochemical, and behavioural studies showing that tyrosine-free amino acid mixtures reduce dopamine function and offer promise for future PET studies testing the effect of tyrosine-depleting paradigms on dopamine release in humans.